TRANSFORMASI ELEMEN-ELEMEN PEMBENTUK KERAJAAN GN. SAHILAN - Praditya, Isag Nabela; Fuadi, Al Busyra; Wongso, Jonny (SIGMA TEKNIKA, 2025)
Development of the Gn. Sahilan since it’s inception, has experienced various important events. The changes in space and time that occur in the timeline are a reflection of life at that time. This research aims to identify the elements that formed the Kingdom of Gn. Sahilan and what factors influence its development. The research was carried out qualitatively using a rationalistic approach, through reading fragments of the timeline drawn diachronically to obtain an overview of the elements that formed the Kingdom of Gn. Sahilan that changes, disappears or survives. Through a period of time, the elements that formed the Kingdom of Gn. Sahilan consists of docks, markets, goods collection points, government areas, industrial areas, residential areas, railway lines, plantations, and circulation patterns. As time went by the elements that formed the Kingdom of Gn. Sahilan experienced development which was influenced by several factors including geographical conditions, technology, globalization, colonial invasion, government regulations, and infrastructure development.